Effects of electrochemotherapy with cisplatin and peritumoral IL-12 gene electrotransfer on canine mast cell tumors - Salvadori, Claudia (Radiology and oncology (Ljubljana), 2017)
The study was aimed to characterize tumor response after combined treatment employing electrochemotherapy with IL-12 gene electrotransfer in dogs with spontaneous mast cell tumors (MCT). Materials and methods. Eleven dogs with eleven MCTs were included in the study. Histological changes were investigated in biopsy specimens collected before the treatment (T0), and 4 (T1) and 8 weeks (T2) later. Cellular infiltrates were characterized immunohistochemically by using anti CD3, CD20, Foxp3 (Treg), CD68 and anti MHC-class II antibodies. Proliferation and anti-apoptotic activity of neoplastic cells were assessed using anti Ki-67 and Bcl-2 antibodies. Angiogenetic processes were investigated immunohistochemically by using anti Factor VIII and anti CD31 antibodies and micro vessel density quantification. Results. Histopathological examination of samples at T0 confirmed the diagnosis and the presence of scanty infiltrates consisted mainly of T-lymphocytes and macrophages. At T1 and T2 neoplastic cells were drastically reduced in 7/11 cases, small clusters of neoplastic cells were detected in 3/11 cases and 1/11 cases neoplastic cells were still evident. Proliferation activity of neoplastic cells was significantly reduced at T1 and T2 and expression of anti-apoptotic protein at T1. Microvessel density was drastically reduced in all samples after treatment. The number of T-lymphocytes increased at T1, although not significant, while Treg were significant higher at T1 and macrophages at T2. Conclusions. The combined electrochemotherapy and IL-12 gene electrotransfer effectively induced a cellular response against neoplastic cells characterized mainly by the recruitment of T-lymphocytes and macrophages and a fibrotic proliferation with reduction of microvessels.
Keywords: electrochemotherapy; elektrokemoterapija; elektroporacija; elektroporation; histopathology; histopatologija; immune cells; imunske celice; interleukin-12; interlevkin 12